Applying Biochar and Oil Palm Seeds' Resistance to Drought Stress - Sri Suryanti; Andre Wibowo; Retni Mardu Hartati (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2023)
Biochar is a soil enhancer because it contains macronutrients and has a high water-holding capacity. Research on the application of biochar and resistance of oil palm seedlings to drought stress was conducted to determine the dosing effect of oil palm shell biochar and watering intervals on the growth of pre-nursery oil palm seedlings under drought stress. The research was conducted in Sialang Godang Village, Bandar Petalangan District, Pelalawan District, Riau Province. The study was conducted in April 2021 – July 2021. The research used a completely randomized design (CRD) with two factors. The first factor was using biochar doses of 5 levels, namely 0 g, 50 g, 100 g, 150 g, and 200 g. The second factor was the watering interval which consisted of 3 groups, i.e.,, watering once a day, every two days, and every three days. Observational data were analyzed using an analysis of variance, and if there was a significant difference, it was continued with the Duncan Multiple Range Test at the 5% level. The results showed that giving biochar at a dose of 200 grams of oil palm shells and watering once every two days significantly increased the fresh weight of roots while providing biochar at a dose of 50 grams of biochar/polybag and watering once every three days significantly increased the dry weight of roots. Watering once every three days significantly increased the number of secondary and tertiary roots, while treatment without biochar and 50 gram/polybag biochar significantly increased the width of stomatal openings. There was a positive correlation between soil moisture content and the number of stomata (r = 0.26), the width of the opening of the stomata, and the dry weight of the roots (r = 0.25).